Hydroponic Screening of Rice Genotypes for Salinity Tolerance at Seedling Stage - Lakshmi , S.; Ravichandran, V.; Anandakumar, S. (Research Highlights in Agricultural Sciences Vol. 8, 2023)
The present aims to evaluate the physiological basis of eight rice genotypes tolerance to salt stress at seedling stage under hydroponic system. Salinity is a major abiotic factor that affects rice cultivation in the world along the coastal areas. The salt affected areas in India is estimated to be around 8 to 10 million hectares that causes significant reduction in rice growth and yield. In order to improve the rice cultivars for salt tolerance, selection of the suitable genotypes is necessitated. The Hydroponics experiment was conducted at Glass house, Department of crop physiology, Tamil Nadu agricultural university, Coimbatore. Study was conducted to screen eight rice genotypes (CO 51, ADT 53, ADT 37, IR 64, CO 43, ASD 16, Pokkali; TRY 3) for salinity tolerance at early seedling stage. Results from this study emanated that that seedling parameters were reduced under saline conditions, Na+ ion Concentration and Na+/ k+ ratio was higher in saline treatments compared to control. However, K+ ion absorption decreased with increasing salinity level. Electrolyte leakage and osmotic potential had increasing trend with increasing salinity. The rice genotypes Pokkali, TRY 3, CO 43 were performed as tolerant; CO 51, ADT 53, ASD 16 were performed as moderately tolerant; ADT 37 was performed as susceptible and IR 64 was performed as highly susceptible. Salt induced osmotic stress leads to physiological drought, causes many disorders and injuries in plant. Ion accumulation also causes change in osmotic potential of plant; to prevent such osmotic imbalance and restrict the entry of sodium and chloride ions into plants. To create genotypes that are tolerant to salt stress during the seedling stage and to increase rice growth and yield in order to meet national requirements, this kind of research is necessary.